The SELF Trial: A self-efficacy based behavioral intervention trial for weight-loss maintenance - Burke, Lora E. (Obesity (Silver Spring), 2015)
OBJECTIVE: The SELF Trial examined the effect of adding individual, self-efficacy (SE) enhancement sessions to standard behavioral weight loss treatment (SBT). METHODS: Participants were randomly assigned to SBT or SBT plus SE sessions (SBT+SE). Outcome measures were weight loss maintenance, quality of life, intervention adherence and self-efficacy at 12 and 18 months. RESULTS: The sample (N=130) was female (83.08%) with a mean (SD) body mass index of 33.15 (4.11) kg/m(2). There was a significant time effect for percent weight change (p=.002), yet no significant group or group-by-time effects. The weight loss for the SBT+SE group was 8.38% (7.48) at 12 months and 8.00% (7.87) at 18 months, with no significant difference between the two time points (p=.06). However, weight loss for the SBT group was 6.95% (6.67) at 12 months and 5.96% (7.35) at 18 months, which was significantly different between the two time points (p=.005) indicating that the SBT group had significant weight regain. CONCLUSIONS: Both groups achieved clinically significant weight loss. The group receiving an intervention targeting enhanced self-efficacy had greater weight loss maintenance whereas the SBT group demonstrated significant weight regain possibly related to the greater attention provided to the SBT+SE group.